Molecular Dynamics Simulations Reveal an Interplay between SHAPE Reagent Binding and RNA Flexibility - Mlýnský, Vojtěch (J Phys Chem Lett, 2017)
[Image: see text] The function of RNA molecules usually depends on their overall fold and on the presence of specific structural motifs. Chemical probing methods are routinely used in combination with nearest-neighbor models to determine RNA secondary structure. Among the available methods, SHAPE is relevant due to its capability to probe all RNA nucleotides and the possibility to be used in vivo. However, the structural determinants for SHAPE reactivity and its mechanism of reaction are still unclear. Here molecular dynamics simulations and enhanced sampling techniques are used to predict the accessibility of nucleotide analogs and larger RNA structural motifs to SHAPE reagents. We show that local RNA reconformations are crucial in allowing reagents to reach the 2′-OH group of a particular nucleotide and that sugar pucker is a major structural factor influencing SHAPE reactivity.